Posing the rationale for synthetic lipoxin mimetics as an adjuvant treatment to gold standard atherosclerosis therapies - Millar, Braden; de Gaetano, Monica (Frontiers in Pharmacology, 2023)
Atherosclerosis is a progressive, multifactorial inflammatory, and dyslipidaemic disease, responsible for the majority of cardiovascular diseases globally. The chronic inflammation is the main driver of the initiation and progression of such disease, as a result of an imbalanced lipid metabolism and an ineffective immune response to attenuate the inflammatory component. The importance of inflammation resolution is being increasingly recognised in atherosclerosis and cardiovascular disease . It has a complex mechanism consisting of multiple stages, including restoring an effective removal of apoptotic bodies (efferocytosis) and their degradation (effero-metabolism), a macrophage phenotype switching towards resolving phenotypes, and the promotion of tissue healing and regeneration. The low-grade inflammation associated with atherosclerosis development is a driving force in disease exacerbation, and hence inflammation resolution is a key area of research. In this review, we explore the complex disease pathogenesis and its many contributing factors to gain a greater understanding of the disease and identify the current and potential therapeutic targets. First-line treatments and their efficacy will also be discussed in detail, to highlight the emerging field of resolution pharmacology. Despite the great efforts made by current gold-standard treatments, such as lipid-lowering and glucose-lowering drugs, they remain ineffective at tackling residual inflammatory risk and residual cholesterol risk. Resolution pharmacology represents a new era of atherosclerosis therapy, as endogenous ligands associated with inflammation resolution are exploited for their pharmacological benefits in a more potent and longer-acting manner. Novel FPR2-agonists, such as synthetic lipoxin analogues, provide an exciting new approach to enhance the pro-resolving response of the immune system and subsequently end the pro-inflammatory response to allow for an anti-inflammatory and pro-resolving environment for tissue healing, regeneration, and return to homeostasis.